Reducing Medical Admissions and Presentations Into Hospital through Optimising Medicines (REMAIN HOME): a stepped wedge, cluster randomised controlled trial. Issue 5 (12th February 2021) - Freeman, Christopher R; Scott, Ian A; Hemming, Karla; Connelly, Luke B; Kirkpatrick, Carl M; Coombes, Ian; Whitty, Jennifer; Martin, James; Cottrell, Neil; Sturman, Nancy; Russell, Grant M; Williams, Ian; et al.
Abstract: Objective: To investigate whether integrating pharmacists into general practices reduces the number of unplanned re‐admissions of patients recently discharged from hospital. Design, setting: Stepped wedge, cluster randomised trial in 14 general practices in southeast Queensland. Participants: Adults discharged from one of seven study hospitals during the seven days preceding recruitment (22 May 2017 ‒ 14 March 2018) and prescribed five or more long term medicines, or having a primary discharge diagnosis of congestive heart failure or exacerbation of chronic obstructive pulmonary disease. Intervention: Comprehensive face‐to‐face medicine management consultation with an integrated practice pharmacist within seven days of discharge, followed by a consultation with their general practitioner and further pharmacist consultations as needed. Major outcomes: Rates of unplanned, all‐cause hospital re‐admissions and emergency department (ED) presentations 12 months after hospital discharge; incremental net difference in overall costs. Results: By 12 months, there had been 282 re‐admissions among 177 control patients (incidence rate [IR], 1.65 per person‐year) and 136 among 129 intervention patients (IR, 1.09 per person‐year; fully adjusted IR ratio [IRR], 0.79; 95% CI, 0.52‒1.18). ED presentation incidence (fully adjusted IRR, 0.46; 95% CI, 0.22‒0.94) and combined re‐admission and ED presentation incidence (fully adjusted IRR, 0.69; 95% CI, 0.48‒0.99) were significantly lower for intervention patients. The estimated incremental net cost benefit of the intervention was $5072 per patient, with a benefit‒cost ratio of 31:1. Conclusion: A collaborative pharmacist‒GP model of post‐hospital discharge medicines management can reduce the incidence of hospital re‐admissions and ED presentations, achieving substantial cost savings to the health system. Trial registration: Australian New Zealand Clinical Trials Registry, ACTRN12616001627448 (prospective).